2009
DOI: 10.1007/s12020-009-9176-0
|View full text |Cite
|
Sign up to set email alerts
|

Progesterone receptors A and B and estrogen receptor alpha expression in normal breast tissue and fibroadenomas

Abstract: Fibroadenomas are the most common benign breast tumors, occurring mainly in young women. Their responses to the hormonal environment are similar to those of normal breast tissue, which suggests that steroid receptors may play a role in tumor development. We evaluated the gene and protein expression of progesterone receptors A and B (PRA and PRB) and the protein expression of estrogen receptor alpha (ER-alpha) in fibroadenoma samples, comparing with adjacent normal breast tissue, from 11 premenopausal women. Pr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
21
1

Year Published

2010
2010
2024
2024

Publication Types

Select...
6
2

Relationship

2
6

Authors

Journals

citations
Cited by 23 publications
(24 citation statements)
references
References 39 publications
2
21
1
Order By: Relevance
“…Previous reports also indicated that ER and PR expression was increased in BBD compared to normal breast at both mRNA and protein levels. (5)(6)(7)9,10,36,37) Results of our present studies are consistent with these results. In addition, our present study also showed significant (P = 0.002 and r = 0.34) positive association between ER and PR immunoreactivity in BBD.…”
Section: P-valuesupporting
confidence: 92%
“…Previous reports also indicated that ER and PR expression was increased in BBD compared to normal breast at both mRNA and protein levels. (5)(6)(7)9,10,36,37) Results of our present studies are consistent with these results. In addition, our present study also showed significant (P = 0.002 and r = 0.34) positive association between ER and PR immunoreactivity in BBD.…”
Section: P-valuesupporting
confidence: 92%
“…50 µg of tissue lysates were applied to a 10% sodium dodecyl sulfate polyacrylamide gel electrophoresis and transferred to a nitrocellulose membrane by electroblotting. The membrane was washed with Tris-buffered saline and Tween 20 blocking solution containing 15 m M NaCl, 5 m M EDTA, 50 m M Tris, 0.5% Tween 20, pH 7.4 + 2.5% BSA, and incubated with specific mouse anti-ERα (66 kDa, F-10; Santa Cruz Biotechnology, Heidelberg, Germany, 1:1,000), rabbit anti-ERβ (56 kDa, H-150; Santa Cruz Biotechnology, 1:500) and mouse anti-aromatase (55 kDa, H4; AbD Serotec, Oxford, UK, 1:1,000) diluted in Tween 20 blocking solution with 2.5% BSA and 0.1% azide [17,18]. The bands were detected by a chemiluminescence reaction with film (CL-Exposure; Pierce) exposure for 15–60 s. The OD of the bands obtained by chemiluminescence was measured by densitometric analysis with an image-processing system (ImageMaster VDS; Pharmacia Biotech).…”
Section: Methodsmentioning
confidence: 99%
“…After this hot start, the reaction was cooled in ice and a mixture of 10 l of the same Tris-HCl buVer and 50 mM MgCl 2 with dNTP mix, sense and antisense primers, and Taq polymerase were added, and submitted to ampliWcation. The characteristics of synthesized oligonucleotides for the ampliWcation of speciWc cDNA fragments are: 2 m sense 5ЈCTATCCAGC GTACTCCAAAG3Ј; 2 m antisense 5ЈACAAGTCTGAA TGCTCCACT30; PRAB sense 5ЈAGAGCACTGGATGC TGTTGCT3Ј; PRAB antisense 5ЈTGGCTTAGGGCTTGG CTTT3Ј; PRB sense 5ЈGCCAGACCTCGGACACCTT3Ј; PRB antisense 5ЈCAGGGCCGAGGGAAGAGTAG3Ј; p53 sense 5ЈAGGTGACCCAGGCTTGGAAG 3Ј; p53 antisense 5ЈTCCTGACTCAGAGGGGGCTC 3Ј; p21 sense 5ЈCTCAG 7AGGAGGCGCCATG 3Ј; p21 antisense 5ЈGGGCGGA TTAGGGCTTCC 3Ј [22,23]. All reagents were from Invitrogen (SuperScript ® PreampliWcation System for First Strand cDNA Synthesis, Invitrogen Biotechnology ™ , Carlsbad, California, USA).…”
Section: Samplesmentioning
confidence: 99%
“…Tissue lysates were applied to a 10% SDS-PAGE and transferred to a nitrocellulose membrane by electroblotting. The membrane was washed with blocking solution (TTBS) containing 15 mM NaCl, 5 mM EDTA, 50 mM TRIS, 0.5% Tween 20, pH 7.4 plus 2.5% BSA, and incubated with speciWc mouse anti-PRs (Santa Cruz Biotechnology ® , Heidelberg, Germany), mouse anti-p53 (BioSource ™ , Carlsbad, California, USA), or mouse anti-p21 (Invitrogen Biotechnology ™ , Carlsbad, California, USA) diluted in TTBS with 2.5% BSA and 0.1% azide [22,23]. The bands were detected by a chemoluminescence reaction (ECL) with Wlm (CL-Exposure ® , Pierce, Rockford, IL, USA) exposure for 15-60 s. The OD of the bands obtained by chemoluminescence was measured by densitometric analysis with an image-processing system (ImageMaster VDS, Pharmacia Biotech ® , Uppsala, Sweden).…”
Section: Western Blotsmentioning
confidence: 99%